THE INFLUENCE OF HERDING, OVERCONFIDENCE, ANCHORING, LOSS AVERSION, RELIGIOSITY ON INVESTMENT DECISIONS MODERATED BY RISK TOLERANCE - Suprapto, Yandi; Tokan, Agnes Doraresta Khatarina (Universitas Nusa Cendana, 2025)
This study aims to analyze the impact of independent variables such as herding bias, overconfidence, anchoring, loss aversion, and religiosity on investment decisions moderated by risk tolerance for investors in Batam City. People who are stock investors in Batam City are the research subjects, with the sampling technique used being snowball sampling. The results showed that factors such as herding bias, overconfidence, anchoring, loss aversion, and religiosity have a significant influence on investment decisions. It is different for the risk tolerance variable, which is not proven to have a significant role in moderating the relationship between the independent variable and the dependent variable, investment decisions. This study also has limitations in terms of samples that may not be able to represent all people who invest in Batam City. Therefore, it is recommended for future research to conduct further research with a more representative sample of the population investing in Batam City. Keywords: Herding; Overconfidence; Anchoring; Loss Aversion; Investment Decision